Identification of filamin C as a new physiological substrate of PKBalpha using KESTREL. - MURRAY, JAMES (My University, 2004)
We detected a protein in rabbit skeletal muscle extracts that was phosphorylated rapidly by PKB ? (protein kinase B ? ), but not by SGK1 (serum- and glucocorticoid-induced kinase 1), and ident- ified it as the cytoskeletal protein FLNc (filamin C). PKB ? phos- phorylated FLNc at Ser 2213 in vitro , which lies in an insert not present in the FLNa and FLNb isoforms. Ser 2213 became phos- phorylated when C2C12 myoblasts were stimulated with insulin or epidermal growth factor, and phosphorylation was prevented by low concentrations of wortmannin, at which it is a relatively specific inhibitor of phosphoinositide 3-kinase. PD 184352 [an in- hibitor of the classical MAPK (mitogen-activated protein kinase) cascade] and/or rapamycin [an inhibitor of mTOR (mammalian target of rapamycin)] had no effect. Insulin also induced the phos- phorylation of FLNc at Ser 2213 in cardiac muscle in vivo , but not in cardiac muscle that does not express PDK1 (3-phosphoinositide- dependent kinase 1), the upstream activator of PKB. These results identify the muscle-specific isoform FLNc as a new physiological substrate for PKB
PUBLISHED
Keywords: protein kinase B (PKB); phosphorylation; kinase substrate tracking and elucidation (KESTREL); filamin; cytoskeleton; Cancer